(click to close)

Please wait

(click to close)

(click to close)

Author:

Justin Stevens

License:

Creative Commons CC BY 4.0
^{(?)}

Abstract:

A lecture on intermediate proofs that I taught at ARML.

Tags:

` ````
\documentclass[12pt,openany]{book}
\setlength{\headheight}{15pt}
\usepackage{amsmath, amsthm, amssymb}
\usepackage{mdframed}
\usepackage{lipsum}
\newmdtheoremenv{thm}{Theorem}[section]
\newmdtheoremenv{exmp}{Example}[section]
\newtheorem*{tips}{Tips}
\theoremstyle{definition}
\newtheorem{defi}{Definition}[section]
\newtheorem*{lemma}{Lemma}
\newtheorem{cor}{Corollary}[section]
\newenvironment{soln}{\begin{proof}[Solution]}{\end{proof}}
\newenvironment{comment}{\begin{proof}[Comment]}{\end{proof}}
\newenvironment{motivation}{\begin{proof}[Motivation]}{\end{proof}}
\newtheorem{psol}{Problem}[section]
\newtheorem{prob}{Problem}[section]
\newtheorem{hint}{Hint}[section]
\usepackage{amsthm,amssymb,amsmath}
\theoremstyle{definition}
\setcounter{section}{1}
\newtheorem*{case}{Example}
\newtheorem{tip}{Tip}[section]
\usepackage{titlesec}
\titleformat{\chapter}[display]
{\normalfont\bfseries\filcenter}
{\LARGE\thechapter}
{1ex}
{\titlerule[2pt]
\vspace{2ex}%
\LARGE}
[\vspace{1ex}%
{\titlerule[2pt]}]
\usepackage{cancel}
\usepackage[margin=4cm]{geometry}
\usepackage{hyperref}
\usepackage{fancyhdr}
\pagestyle{fancy}
\fancyhead{}
\fancyfoot{}
\lhead{Intermediate Proofs}
\chead{Justin Stevens}
\rhead{Page \thepage}
\newenvironment{dedication}
{\vspace{6ex}\begin{quotation}\begin{center}\begin{em}}
{\par\end{em}\end{center}\end{quotation}}
\newcommand{\HRule}{\rule{\linewidth}{0.5mm}} % Defines a new command for the horizontal lines, change thickness here
\title{ARML Lecture: Telescoping Series}
\begin{document}
% Center everything on the page
%----------------------------------------------------------------------------------------
% TITLE SECTION
%----------------------------------------------------------------------------------------
\begin{center}
\HRule \\[0.4cm]
{ \huge \bfseries ARML: Intermdiate Proofs}\\[0.4cm] % Title of your document
\HRule \\[1.5cm]
\begin{minipage}{0.4\textwidth}
\begin{flushleft} \large
\emph{Authors}\\
Justin \textsc{Stevens} \newline
\end{flushleft}
\end{minipage}
~
\begin{minipage}{0.4\textwidth}
\begin{flushright} \large
\end{flushright}
\end{minipage}\\[0.5cm]
\end{center}
\chapter{Intermediate Proofs}
\section{Lecture}
There are several methods used in Intermediate Proofs:
\textbf{Contradictions:} If we want to show that $A$ is true, we use proof by contradiction by showing that if $A$ is false, then that would result in an impossibility, thereby resulting in $A$ being true.
\textbf{Induction:} Let's say we want to prove a statement $P(n)$ for positive integer $n$, with $n_0$ being a fixed positive integer. If $P(n_0)$ is true and $P(k+1)$ is true whenever $P(k)$ is, then $P(n)$ is true for $n\ge n_0$.
\textbf{Strong Induction:} Let's say we want to prove a statement $P(n)$ for positive integers $n$, with $n_0$ being a fixed positive integer. If $P(n_0)$ is true and $P(k+1)$ is true whenever $P(m)$ is for $n_0 \le m\le k$, then $P(n)$ is true for $n\ge n_0$.
We'll cover these all in depth throughout this lesson.
\begin{exmp} Prove that there are infinitely many prime numbers. \end{exmp}
\begin{soln} We proceed by proof by contradiction. Assume that there are only a finite number of prime numbers, namely $p_1, p_2, \cdots, p_k$. Consider the number $M=p_1p_2\cdots p_k+1$. Clearly, $M$ is not divisible by $p_i$ for $1\le i\le k$, therefore $M$ must be divisible by a prime which is not in our assumed set of primes, contradiction. There are therefore infinitely many primes. \end{soln}
\begin{exmp} Prove that there does not exist integers $a,b$ such that $a^2-4b=2$. \end{exmp}
\begin{soln} Assume for the sake of contradiction that there are integers $a,b$ that satisfy the above equation. Rearranging the equation, we see that $a^2=2+4b=2(1+2b)$. Therefore, $a$ must be even. Let $a=2a_0$ for some $a_0$. Substituting this back into the equation gives us $$(2a_0)^2=2(1+2b)\implies 4a_0^2=2+4b\implies 2a_0^2=1+2b$$
However, $2a_0^2$ and $2b$ are both even, while $1$ is not, therefore the above equation is a contradiction mod $2$.
\textit{Note:} Some more experienced problem solvers may have instantly noted that the above equation is a contradiction mod $4$ since the possible residues mod $4$ are $0,1$.
\end{soln}
\begin{exmp} Prove that $\sqrt{2}$ is irrational. \end{exmp}
\begin{soln} Assume for the sake of contradiction that $\sqrt{2}$ is rational. Therefore $\sqrt{2}=\frac{a}{b}$ for relatively prime $a,b$. Squaring the equation and multiplying by $b^2$ on both sides gives us $a^2=2b^2$. Therefore, $2\mid a$ and $a=2a_0$ for some $a_0$. Substituting this back into the equation, we have $$4a_0^2=2b^2\implies 2a_0^2=b^2$$ Similarly, since the left hand side of the equation is even, $b$ must also be even and $b=2b_0$ for some $b_0$. However, $\gcd(a,b)=2\gcd(a_0, b_0)$, contradicting the assumption that $a$ and $b$ were relatively prime. Contradiction. Therefore $\sqrt{2}$ is irrational. \end{soln}
\begin{exmp} Prove that for $x\in [0, \frac{\pi}{2}]$, $\sin(x)+\cos(x)\ge 1$. \end{exmp}
\begin{soln} Assume for the sake of contradiction that $\sin(x)+\cos(x)<1$. Squaring this gives $$\left(\sin(x)+\cos(x)\right)^2<1\implies \sin^2(x)+\cos^2(x)+2\sin(x)\cos(x)<1\implies 2\sin(x)\cos(x)<0$$
With the last step following from the Pythagorean Identity that $\sin^2(x)+\cos^2(x)=1$. However, $x\in [0, \frac{\pi}{2}]$, therefore $2\sin(x)\cos(x)\ge 0$, contradiction. Therefore for $x\in [0, \frac{\pi}{2}], \sin(x)+\cos(x)\ge 1$. \end{soln}
\begin{exmp} Prove the identity $1+2+2^2+\cdots +2^n=2^{n+1}-1$. \end{exmp}
\begin{soln}
\textbf{Base Case:} When $n=1$, we get $1+2^1=2^{2}-1$, which is true.
\textbf{Inductive Hypothesis:} Assume that the problem statement holds for $n=k$. We show that it then also holds for $n=k+1$.
Notice that $$1+2+2^2+\cdots+2^{k+1}=\left(1+2+2^2+\cdots+2^k\right)+2^{k+1}$$
Now, using the inductive hypothesis, $1+2+\cdots+2^k=2^{k+1}-1$. Substituting this into the above equation gives us $$1+2+2^2+\cdots+2^{k+1}=\left(2^{k+1}-1\right)+2^{k+1}=2^{k+2}-1$$
Our induction is complete, and $1+2+2^2+\cdots+2^n=2^{n+1}-1$ for all non-negative $n$. \end{soln}
\begin{exmp} Prove that $1\cdot 1!+2\cdot 2!+3\cdot 3!+\cdots+n\cdot n!=(n+1)!-1$ \end{exmp}
\begin{soln}
\textbf{Base Case:} When $n=1$, $1\cdot 1!=\left(1+1\right)!-1$, which is true.
\textbf{Inductive Hypothesis:} Assume that the problem statement holds for $n=k$. We show that it holds for $n=k+1$. Notice that $$1\cdot 1!+2\cdot 2!+3\cdot 3!+\cdots+k\cdot k!+(k+1)\cdot (k+1)!=\left(1\cdot 1!+2\cdot 2!+3\cdot 3!+\cdots+k\cdot k!\right)+(k+1)\cdot (k+1)!$$
Using the inductive hypothesis, $1\cdot 1!+2\cdot 2!+\cdots+k\cdot k!=(k+1)!-1$. Substituting this into the above equation, $$1\cdot 1!+2\cdot 2!+3\cdot 3!+\cdots+(k+1)\cdot (k+1)!=(k+1)!-1+(k+1)\cdot (k+1)!=(k+2)(k+1)!-1=(k+2)!-1$$
\end{soln}
\begin{exmp} Show that if $n$ is a positive integer greater than $2$, then $$\frac{1}{n+1}+\frac{1}{n+2}+\cdots+\frac{1}{2n}>\frac{3}{5}$$ \end{exmp}
\begin{soln} Notice that the problem statement says for $n$ being a positive integer \textbf{greater than 2}, therefore the base case is $3$ rather than $1$ (\textit{in the formal definition of induction given above, } $n_0=3$).
\textbf{Base Case:} When $n=3$, $$\frac{1}{4}+\frac{1}{5}+\frac{1}{6}=\frac{37}{60}>\frac{36}{60}=\frac{3}{5}$$
\textbf{Inductive Hypothesis:} Assume the statement holds for $n=k$. Then, we show that it also holds for $n=k+1$.
Notice that
$$\frac{1}{k+2}+\frac{1}{k+3}+\cdots+\frac{1}{2k+2}=\frac{1}{k+1}+\frac{1}{k+2}+\cdots+\frac{1}{2k}+\left(\frac{1}{2k+1}+\frac{1}{2k+2}-\frac{1}{k+1}\right)$$
Using the Inductive Hypothesis, $\frac{1}{k+1}+\frac{1}{k+2}+\cdots+\frac{1}{2k}>\frac{3}{5}$, therefore, substituting this into the above equation gives us \begin{eqnarray*} \frac{1}{k+2}+\frac{1}{k+3}+\cdots+\frac{1}{2k+2}&>&\frac35+\frac{1}{2k+1}+\frac{1}{2k+2}-\frac{1}{k+1} \\ &=& \frac35+\frac{1}{2k+1}-\frac{2}{2k+2}+\frac{1}{2k+2} \\ &=& \frac35+\frac{1}{2k+1}-\frac{1}{2k+2} \\ &=& \frac35+\frac{1}{(2k+1)(2k+2)} \end{eqnarray*}
Now, using the fact that $\frac{1}{(2k+1)(2k+1)}>0$, we get $$\frac{1}{k+2}+\frac{1}{k+3}+\cdots+\frac{1}{2k+2}>\frac35+\frac{1}{(2k+1)(2k+2)}>\frac35$$
We are done by induction. \end{soln}
\begin{exmp} The Fibonacci sequence is defined by $F_{1}=F_2=1$, and $F_n=F_{n-1}+F_{n-2}$ for all $n\ge 3$. Prove that every positive integer $N$ can be represented by $$N=F_{a_1}+F_{a_2}+\cdots+F_{a_m}$$ for some integers $a_1, a_2, \cdots, a_m$ satisfying $2\le a_1<a_2<\cdots<a_m$. \end{exmp}
\begin{soln} The base case of $N=1=F_2$ is trivial. To get a feel for the problem, consider the number $N=79$. How would we go about representing this as a sum of Fibonacci numbers? Well, the smallest Fibonacci number less than $79$ is $55$. Subtract gives $79-55=24$. We then repeat this procedure. The smallest Fibonacci number less than $24$ is $21$. Subtracting yields $24-21=3$. Finally, $3=2+1=F_3+F_2$. Therefore, $79=55+21+3+1=F_{10}+F_8+F_3+F_2$.
We think of how to generalize this method. In a regular induction problem, we would assume that it holds for $N=K$ and show that it holds for $N=K+1$. However, in the above example, once we subtract $55$ we are left with a number close to $K$ but less than it. This therefore queues for us to use strong induction.
\textbf{Inductive Hypothesis:} Assume that the problem statement holds for all positive integers from $1$ to $K$. We show that the problem statement holds for $K+1$.
Let $F_a$ be the largest Fibonacci number with $F_a\le K+1$. If $F_a=K+1$, then we are clearly done. Otherwise, $F_a<K+1<F_{a+1}$, therefore $$0<(K+1)-F_a<F_{a+1}-F_a=F{a-1}$$
Now, by our inductive hypothesis, $(K+1)-F_a=F_{b_1}+F_{b_2}+\cdots+F_{b_m}$. Furthermore, since $(K+1)-F_a<F_{a-1}$, we have that $2\le b_1<b_2<\cdots<b_m<a$. Therefore, $K+1=F_a+F_{b_1}+F_{b_2}+\cdots+F_{b_m}$ satisfies the desired condition. \end{soln}
\section{Problems for the Reader}
\begin{prob} Prove that $\sqrt[3]{3}$ is irrational. \end{prob}
\begin{prob} Prove that there are infinitely many primes of the form $4k+3$. \end{prob}
\begin{prob} Prove that if $a^2-2a+7$ is even, then $a$ must be odd. \end{prob}
\begin{prob} Prove that the product of $5$ consecutive integers is divisible by $120$. \end{prob}
\begin{prob} Prove that the number $\log_{2}3$ is irrational. \end{prob}
\begin{prob} Prove that if $4\mid (a^2+b^2)$ and $a$ and $b$ are both positive integers, then $a$ and $b$ cannot both be odd. \end{prob}
\begin{prob} Prove that there are no rational roots to the equation $x^3+x+1=0$. \end{prob}
\begin{prob} Prove that there are no $(x,y)\in \mathbb{Q}^2$ (\textit{meaning x and y are rational}) such that $x^2+y^2-3=0$. \end{prob}
\begin{prob} Prove that if $a,b,c$ are odd integers, then the equation $ax^2+bx+c=0$ does not have any integer roots. \end{prob}
\begin{prob} Prove that the sum of the first $n$ positive integers is $\frac{n(n+1)}{2}$. \end{prob}
\begin{prob} Prove that $$\frac{m!}{0!}+\frac{(m+1)!}{1!}+\frac{(m+2)!}{2!}+\cdots+\frac{(m+n)!}{n!}=\frac{(m+n+1)!}{n!(m+1)}$$ \end{prob}
\begin{prob} The $k$th triangular number is equivalent to $\frac{k(k+1)}{2}$. Prove that the sum of the first $n$ triangular numbers is $\frac{n(n+1)(n+2)}{6}$. \end{prob}
\begin{prob} Show that if $n$ is a positive integer, then $1+\frac{1}{\sqrt2}+\frac{1}{\sqrt3}+\cdots+\frac{1}{\sqrt{n}}<2\sqrt{n}$. \end{prob}
\begin{prob} Use induction and/or telescoping sums to prove that $\frac{1}{1\cdot 3}+\frac{1}{3\cdot 5}+\frac{1}{5\cdot 7}+\cdots +\frac{1}{(2n-1)(2n+1)}=\frac{n}{2n+1}$. \end{prob}
\begin{prob} The sequence $x_1, x_2, x_3, \cdots$ is defined by $x_1=2$ and $x_{k+1}=x_k^2-x_k+1$ for all $k\ge 1$. Find $\sum_{k=1}^{\infty} \frac{1}{x_k}$. \end{prob}
\begin{prob} Prove that $n^4\le 4^n$ for all positive integers $n$ greater than $3$. \end{prob}
\begin{prob} Let $x+\frac{1}{x}=a$, for some integer $a$. Prove that $x^n+\frac{1}{x^n}$ is an integer for all $n\ge 0$. \end{prob}
\begin{prob} Show that the $n$th Fibonacci number, $F_n=\binom{n-1}{0}+\binom{n-1}{1}+\cdots$ \end{prob}
\begin{prob} On a large, flat field $n$ people are positioned so that for each person the distances to all the other people are different. Each person holds a water pistol and at a given signal fires and hits the person who is closest. When $n$ is odd show that there is at least one person left dry. Is this always true when $n$ is even? \end{prob}
\begin{prob} Prove that for all natural $n$, that $\frac{1}{1^2}+\frac{1}{2^2}+\frac{1}{3^2}+\cdots+\frac{1}{n^2}<2$. \end{prob}
\end{document}
```

Something went wrong...

Our gallery is the easiest way to put your LaTeX templates, examples and articles online. Just create a free project and use the publish menu. It only takes a couple of clicks!

The LaTeX templates, examples and articles in the Overleaf gallery all come from our amazing community.

New content is added all the time. Follow us on twitter for the highlights!